2016
DOI: 10.1016/j.jece.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Dyes decolorization using silver nanoparticles supported on nanometric diamond as highly efficient photocatalyst under natural Sunlight irradiation

Abstract: Herein we report that silver nanoparticles supported on commercial diamond nanoparticles functionalized with hydroxyl groups (D3) is a cost-effective heterogeneous catalyst for the decolorization of different synthetic dyes (Methylene Blue, Orange II, Acid Red 1 or Rhodamine B) using H2O2 as oxidant under natural Sunlight irradiation. Importantly, the photocatalytic activity of Ag/D3 is higher than that of analogous catalysts based on Ag NPs supported on graphite or activated carbon and similar to that of cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Besides acids and bases, homogeneous and heterogeneous catalysis is currently dominated by the use of transition metals, either as free ions, coordination metal complexes, clusters or nanoparticles, acting as active sites. [1][2][3][4][5][6][7][8][9][10][11][12][13] Some of these transition metals are rare, there being issues of sustainability coming with such choices. There is a large incentive in finding alternative metalfree catalysts, based on abundant elements.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…Besides acids and bases, homogeneous and heterogeneous catalysis is currently dominated by the use of transition metals, either as free ions, coordination metal complexes, clusters or nanoparticles, acting as active sites. [1][2][3][4][5][6][7][8][9][10][11][12][13] Some of these transition metals are rare, there being issues of sustainability coming with such choices. There is a large incentive in finding alternative metalfree catalysts, based on abundant elements.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…Commonly, D NPs are functionalized with oxygen-functional groups for the production of catalysts with enhanced catalytic activity. Several works have demonstrated that the presence of specific oxygen functional groups on D NPs is a prerequisite for the deposition of small MNPs , or for the covalent anchorage of organic molecules or metal complexes and the development of active catalysts. A few examples have also shown that oxygen functional groups such as carboxylates can coordinate metal ions such as Ni 2+ , Cu 2+ , or Fe 2+ , and then these can be used as catalysts for the oxidation of organic compounds in the presence of H 2 O 2 as oxidant …”
Section: Modification Of D Nps For Catalytic Applicationsmentioning
confidence: 99%
“…Los cambios en los espectros UV-Vis, junto con la remoción de ~ 80 % de la DQO después de 180 min de tratamiento indican que las especies oxidantes generadas en el proceso fotocatalítico (huecos y radicales oxidantes) degradan los colorantes mediante ataques a los grupos cromóforos, para generar compuestos más oxidados que las sustancias de partida. La línea espectral demuestra también la eliminación de la banda visible (a 470 nm), y el incremento inicial de la banda ubicada a 190 nm sugiere que el sistema en las primeras etapas induce la ruptura de los grupos azo de los colorantes junto a la formación de grupos tipo ácido carboxílico (los cuales presentan fuertes absorciones alrededor de los 190 nm) (Manickam-Periyaraman et al, 2016). Como se ha reportado en la literatura (Rubio-Clemente et al, 2014), dichos ácidos pueden ser subsecuentemente removidos por la acción de los huecos a través del proceso foto-Kolbe, lo cual explica el decrecimiento de la banda a 190 nm a los tiempos más altos del tratamiento.…”
Section: Fotocatálisis Con Tio 2 En El Reactor Tipo Batch Y Con Luz Sunclassified
“…Estos resultados indican que el proceso está transformando los contaminantes en compuestos más oxidados que los colorantes iniciales. De hecho, mediante el tratamiento con fotocatálisis con TiO 2 los colorantes naranja G o rojo ácido G (colorantes tipo azo como los aquí estudiados) experimentan trasformaciones estructurales tales como la generación de dobles enlaces de oxígeno con los nitrógenos de los grupos azo, la hidroxilación de anillos aromáticos, la ruptura de anillos y la formación de ácidos carboxílicos, además de la desulfonación (Manickam-Periyaraman et al, 2016;Sakkas et al, 2010;Teh & Mohamed, 2011), lo que demuestra el poder oxidante del proceso.…”
unclassified